Oxygen exchange at gas/oxide interfaces: how the apparent activation energy of the surface exchange coefficient depends on the kinetic regime. Issue 32 (27th July 2016) - Fielitz, Peter; Borchardt, Günter
Abstract : The model explains the range of apparent activation energies measured in different kinetic regimes of oxygen exchange at oxide surfaces. Abstract : In the dedicated literature the oxygen surface exchange coefficient K O and the equilibrium oxygen exchange rate 0O are considered to be directly proportional to each other regardless of the experimental circumstances. Recent experimental observations, however, contradict the consequences of this assumption. Most surprising is the finding that the apparent activation energy of K O depends dramatically on the kinetic regime in which it has been determined, i.e. surface exchange controlled vs. mixed or diffusion controlled. This work demonstrates how the diffusion boundary condition at the gas/solid interface inevitably entails a correlation between the oxygen surface exchange coefficient K O and the oxygen self-diffusion coefficient D O in the bulk ("on top" of the correlation between K O and 0O for the pure surface exchange regime). The model can thus quantitatively explain the range of apparent activation energies measured in the different regimes: in the surface exchange regime the apparent activation energy only contains the contribution of the equilibrium exchange rate, whereas in the mixed or in the diffusion controlled regime the contribution of the oxygen self-diffusivity has also to be taken into account, which may yield significantly higher apparent activation energies and simultaneously quantifies the correlation K O ∝ D O 1/2 observed for a large number of oxides in the mixed or diffusion controlled regime, respectively.